The Effect of Digital Textbooks on Comprehension Performance in Inclusive Science Classrooms - Alzahrani, Turkey (Journal of Posthumanism, 2025)
The purpose of this study was to examine the impact of digital textbooks versus traditional textbooks on comprehension performance and application in secondary inclusive classrooms. The sample comprised of 121 sixth grade students, in six science class periods, which were divided into three groups. Using a control/treatment quasi-experimental counterbalanced design, the study was conducted through two phases; in phase 1, group 1 was the treatment (received the digital textbook), while groups 2 and 3 were the control (received the traditional textbook); in phase 2, groups 1 and 2 switched, while group 3 remained in the control group. Across both phases, there was no statistically significant difference in comprehension performance between both groups. In regard to application, there was also no statistically significant difference between groups in Ecocolumn project, but there was a significant difference in regard to Food Web project. The limitations and implications of the study are discussed.